Understanding the perspectives of people with dementia and family carers about clinical pharmacists in primary care: A qualitative study - Alice Burnand; Abi Woodward; Kumud Kantilal; Cini Bhanu; Yogini Jani; Jill Manthorpe; Mine Orlu; Greta Rait; Madiha Sajid; Kritika Samsi; Victoria Vickerstaff; Jane Ward; et al. (PLoS ONE, 2025)
Background The number of people living with dementia is increasing, placing significant strain on healthcare systems and family carers. Primary care teams, including clinical pharmacists, are crucial in supporting people with dementia. While clinical pharmacists have demonstrated benefits in other areas of healthcare, their role in dementia care is less understood. This study aims to explore the perspectives of people with dementia and family carers on the potential contributions of clinical pharmacists to dementia support within primary care in England. Objectives To explore the views and perspectives of people with dementia and family carers of dementia care received from primary care teams, with a specific focus on clinical pharmacists in England. Methods We conducted thirteen semi-structured interviews with family carers and fifteen with people with dementia in 2022–2024. Interviews were analysed using reflexive thematic analysis. Results Three overarching themes, were developed from the interviews: 1) Recognising the value of clinical pharmacists 2) Building and developing rapport, with personalised care and a holistic approach; and 3) The needs of patients without clinical pharmacy support – left in uncertainty about their care. Conclusion This study highlights the potential of clinical pharmacists in dementia care, highlighting both positive experiences as well as unmet needs of those who did not have access to the service. Awareness of these services hinder the impact that they might be able to achieve otherwise. Increasing awareness, standardising training, and further research on service delivery models are crucial.